Analisis Faktor-faktor yang Mempengaruhi Keinginan Masyarakat untuk Menerima Perbankan Syariah - Reni Yendrawati; Achmad Tirto Sudiro (Jurnal Aplikasi Bisnis, 2017)
This research titled "Analyzes the Factors that have an Effect Towards Society Intention to Accept on Islamic" which is purposed to test the factors that influent the Intention to accept of society into Islamic Banking as an alternative of financial. This research use source not only from Indonesian research and literature but also from foreign research and literature which is focus om internal variable, economic factors and religious factors also external variable that is quality of service, geographic acces and brand then test the influence of each its variable into the dependent variable which is intention to accept. Test on ths research use doubled regression formula.This research takes sample society on Daerah Istimewa Yogyakarta. Sampling based on society jobs which classified into four class that are Mahasiswa, Pegawai Negeri Sipil, Pegawai Swasta and UKM (Usaha Kecil dan Menengah). It's use accidental sampling technic, that spread 200 of quesiner but only 134 that can be process. Data were analyzed using statistical software SPSS version 16.0 and AMOS version 16.0.From five hypothesis only one that prove influencing the intention to accept on Islamic Banking. It's show that Daerah Istimewa Yogyakarta society intention to accept on Islamic Banking as an altenative of financial institutions only influenced by religious factors not economic factors, quality of service, geographic acces or brand.